Comparison of Complication Rates with and without Arch Bar Use in Treatment of Mandible Fractures. (23rd August 2013) - Archer, Kaete A.; Kopp, Robert; Goyal, Parul; Kellman, Robert M.; Suryadevara, Amar C.
Abstract : Objectives: 1) Explain the pros and cons of using arch bars for mandible fracture stabilization. 2) Compare and contrast the outcomes of mandible fractures treated with and without arch bars. Methods: A retrospective review was performed of mandible fractures treated at a Level 1 trauma center between 2001 and 2011. Two‐hundred forty‐two patients met inclusion criteria. Patients were categorized into those treated with or without arch bars. Major complications were malocclusion, infection, and malunion. Independent variables of age, sex, trauma, and dental status were collected. Exclusion criteria included lack of follow‐up, greenstick fractures, mid‐facial fractures, and subcondylar fractures. Data were analyzed using Fisher's exact test. Results: Eighty‐four patients had one mandible fracture, and 158 patients had two fractures. Overall, patients treated with arch bars had a complication rate of 13%, and those treated without arch bars had a rate of 16%. This was statistically insignificant ( P = 0.58). When separated by number of fractures, the differences remained insignificant (12% and 10% complication rates with and without arch bars in single fracture cases ( P = 0.74); 14% and 19% in two fracture cases ( P = 0.37)). Conclusions: The use of arch bars did not have a significant effect on major complications in this series. This trend was consistent for cases of one and two mandible fractures. These data suggest that many patients with mandible fractures may be safely treated without arch bars.